Novel Antimicrobial Titanium Dioxide Nanotubes Obtained Through a Combination of Atomic Layer Deposition and Electrospinning Technologies - Escrig-Murua, J; Galotto-Lopez, M; Alburquenque-Munoz, D; Alburquenque-Munoz, D; Lopez de Dicastillo-Bergamo, A; Patiño-Vidal, C (Multidisciplinary Digital Publishing Institute (MDPI), 2018)
The search for new antimicrobial substances has increased in recent years. Antimicrobial nanostructures are one of the most promising alternatives. In this work, titanium dioxide nanotubes were obtained by an atomic layer deposition (ALD) process over electrospun polyvinyl alcohol nanofibers (PVN) at different temperatures with the purpose of obtaining antimicrobial nanostructures with a high specific area. Electrospinning and ALD parameters were studied in order to obtain PVN with smallest diameter and highest deposition rate, respectively. Chamber temperature was a key factor during ALD process and an appropriate titanium dioxide deposition performance was achieved at 200◦ C. Subsequently, thermal and morphological analysis by SEM and TEM microscopies revealed hollow nanotubes were obtained after calcination process at 600◦ C. This temperature allowed complete polymer removal and influenced the resulting anatase crystallographic structure of titanium dioxide that positively affected their antimicrobial activities. X-ray analysis confirmed the change of titanium dioxide crystallographic structure from amorphous phase of deposited PVN to anatase crystalline structure of nanotubes. These new nanostructures with very large surface areas resulted in interesting antimicrobial properties against Gram-positive and Gram-negative bacteria. Titanium dioxide nanotubes presented the highest activity against Escherichia coli with 5 log cycles reduction at 200 µg/mL concentration. © 2018 by the authors. Licensee MDPI, Basel, Switzerland.